HEALTH QUARANTINE AS PILGRIM RISK CONTROL DURING THE 2026 HAJJ EMBARKATION PHASE - Rosidi Roslan (jfpublisher, 2026)
Introduction. The Hajj pilgrimage is among the largest religious mass gatherings globally, in which the embarkation phase serves as the final health risk control point before pilgrims depart for Saudi Arabia, integrating health examination, istithaah assessment, fitness to fly determination, vaccination, environmental sanitation, and catering oversight as a unified safety system. Method. This study applied an integrative literature review with descriptive document analysis using two official 1447 H/2026 Hajj embarkation surveillance documents from the Directorate of Surveillance and Health Quarantine, Ministry of Health of the Republic of Indonesia, supplemented by peer-reviewed literature. Analysis combined descriptive statistics, content analysis, narrative synthesis, and cross-document triangulation. Result & Analysis. All twenty embarkation units reported through SINKARKES at full compliance, covering over five hundred flight groups and more than two hundred thousand registered pilgrims. Most pilgrims carried comorbid conditions, yet the majority were classified as eligible or eligible with accompaniment under the istithaah framework. Illness and hospitalisation were the dominant reasons for deferred and cancelled departures. Vaccination occurred primarily at the region of origin, while environmental sanitation and catering inspections achieved full compliance across all units. Discussion. The embarkation phase functions as a structured pre-event risk control mechanism within the mass gathering health framework, wherein health examination, aggregate surveillance, vaccination verification, and environmental and food safety oversight collectively constitute a comprehensive instrument of pilgrim safety prior to international departure.